Solid-State Metathetic Synthesis of Strontium Molybdate Particles Assisted by Microwave Irradiation - Oh, Won-Chun; Yeon Park, Chong; Won Jeon, Jeong; Sung Lim, Chang (Asian Journal of Chemistry, 2012)
A solid-state metathetic route was used to synthesize strontium molybdate (SrMoO4) particles assisted by microwave irradiation under environmentally friendly conditions. The SrMoO4 particles were synthesized successfully using the solid-state metathetic method with microwave irradiation. Well crystallized SrMoO4 particles were formed at 600 ºC for 3 h, showing a spherical and homogeneous morphology with sizes of 0.5-1 μm. The solid-state metathetic reaction of the SrMoO4 particles is discussed in detail based on the exothermic reaction. The synthesized SrMoO4 particles were characterized by X-ray diffraction, Fourier transform infrared spectroscopy and scanning electron microscopy. The optical properties were investigated by photoluminescence emission and Raman spectroscopy.